School Leadership: A comparison of Singaporean and Indian cases - Retna, Kala; Jeyavelu, S (School of Management Working Papers, 2010)
The role of the principal in transforming a school is a core theme within the education literature on leadership. However, such work is mostly developed in a „Western‟ cultural environment, representing a particular set of values. This ignores the possibility that although leadership may be universal, the way it is described and practised may differ from culture to culture. Drawing from research carried out in Singapore and India, we present in this article how the teachers and students perceive the transformational effects of the school principals from an organisational and cultural perspective. This qualitative research uses in-depth interviews supplemented by participant observations to understand the influence of cultural variables on the practice of transformational leadership. In one case, despite cultural tensions, the findings suggest that the practice of transformational leadership has facilitated a positive culture in terms of collective learning and connectedness to the workplace and a leader among the organisational members. In the other case, transformational actions influenced sharing and learning and enhanced motivation where the leader consciously focused on creating a culture through actions aimed at achieving the vision which itself was in tune with the context.